THE CRISIS OF IDENTITY IN PURSUING THE AMERICAN DREAM IN GIRL IN TRANSLATION BY JEAN KWOK - Indira, Omega Meisagawa; Dieni, Novita Al Ihyak (LINGUAMEDIA Journal, 2023)
ABSTRACT The United States is a continent full of immigrants. Immigrants are always related to identity issues and cultural adaptation due to diverse backgrounds. The life of immigrants is remarkably interesting to discuss, especially the problems they faced and the process of accepting their lives in the host country. Therefore, this paper will discuss the identity crisis experienced by the main character in pursuing the American dream in Girl in Translation. There are two objectives to be achieved in this study. The first objective is to find out the identity crisis experienced by the main character in Girl in Translation. The second objective is to find out how the main character overcomes the problems she faced. To achieve the objectives of the study, the writer will use mimetic theory as an approach. The method that will be used is qualitative method. Based on the analysis, it can be found that the main character experiences the identity crisis through language, dwelling, food, clothes, lifestyle, and moral. To overcome the identity crisis, the main character uses hybrid identity. The mixed identities make the main character become a Chinese-American. Keywords: main character; identity crisis; the American dream; Chinese immigrants; American culture.